No evidence to implicate Borrelia burgdorferi in the pathogenesis of dilated cardiomyopathy in the United Kingdom. Issue 5 (May 1994) - Rees, D. H.; Keeling, P. J.; McKenna, W. J.; Axford, J. S.
Abstract : OBJECTIVE–To determine whether Borrelia burgdorferi is implicated in the pathogenesis of dilated cardiomyopathy in the United Kingdom. DESIGN–A controlled prospective study. Patients' notes were reviewed for evidence of Lyme disease and serum samples were tested by enzyme linked immunoadsorbent assay (ELISA) for antibodies to B burgdorferi. Samples with raised antibody concentrations were subsequently analysed by immunoblotting to determine their antibody binding specificity. SETTING–Tertiary referral centre. PATIENTS–97 consecutive patients with dilated cardiomyopathy diagnosed according to World Health Organisation criteria were studied. Serum samples were taken from two matched control groups. The first group (n = 38) was age, sex, and geographically matched. The second control group (n = 39) was environmentally matched and consisted of members of the patients' own households. MAIN OUTCOME MEASURES–Clinical evidence of Lyme disease. Presence of raised antibody concentrations to B burgdorferi. RESULTS–No patients had a previous illness compatible with Lyme disease. Analysis of the ELISA data showed eight of 97 patients with dilated cardiomyopathy (8.2%) and two of 77 controls (3.9%) had raised antibody concentrations. Immunoblot analysis, however, did not show binding patterns consistent with the presence of IgG specific for B burgdorferi in any of these samples. CONCLUSIONS–There was no clinical or serological evidence to implicate B burgdorferi in the pathogenesis of idiopathic dilated cardiomyopathy in the United Kingdom. In the absence of specific symptoms or likely exposure to B burgdorferi routine serological testing for Lyme disease in this group of patients is not recommended. Furthermore, raised antibodies to B burgdorferi are not diagnostic of active infection and ELISA results should be interpreted with caution unless specific B burgdorferi antibody bands have been found by immunoblot analysis.